Study on the East Syriac Anaphorae and Their Theological Implications - DUAN, Wenjunyi (Journal of Research for Christianity in China (JRCC), 2025)
The East Syriac liturgy is one of the major liturgical traditions within Christianity. Its anaphorae, as the central prayer of the Sacrament of the Eucharist, bears rich theological meaning and a profound ecclesiastical tradition. This study compares the structure and content of the three principal East Syriac anaphorae, which are attributed to Mar Addai and Mari, Mar Theodore and Mar Nestorius, revealing their shared structure and thematic elements. Special focus is given to the Anaphora of Mar Theodore the Interpreter, examining its textual composition and theological implications. This paper highlights the central role of the epiclesis in all three anaphorae, particularly emphasizing the Spirit’s divine power in the consecration of bread and wine. Furthermore, it explores the interpretations of this prayer by Gabriel of Qatar and Yohannan Bar Zoˁbi, unveiling the religious significance of the epiclesis in the East Syriac rite and illustrating the distinctive liturgical theology of the Church of the East.
Keywords: Liturgy, Anaphora, the Church of the East, Jingjiao, the East Syriac Christianity